A Markov model assessing the impact on primary care practice revenues and patient's health when using mid‐level providers, lesson learned from the United Kingdom. (8th March 2017) - Hill, Harry; Macey, Richard; Brocklehurst, Paul
Abstract: Objective: To evaluate the cost‐effectiveness of using mid‐level providers for dental "check‐up" examinations and the treatment of caries in different NHS settings in the United Kingdom. Mid‐level providers are a broad category that describes non‐dentist members of dental teams. This study focused on the potential use of Dental Hygiene Therapists undertaking dental "check‐up" examinations and simple restorative treatment, instead of dentists. Methods: A Markov model was used to construct the natural history of caries development in adults that visit a dental practice every six months over a five‐year period. Three cost perspectives are taken: those borne to dental healthcare providers in England and Wales, Northern Ireland and Scotland. These represent three separate forms of retrospective payment system that are currently in use in the United Kingdom. The cost outcome was the average amount of retained practice earnings required to provide healthcare per patient visit. The health outcome was the average length of time in a cavity‐free state and the cost‐effectiveness outcome was incremental cost for six months in a cavity‐free state. Results: No statistical difference was found between dentists and mid‐level providers in the length of time in a cavity‐free state but the use of the latter saved money in all three NHS health system jurisdictions. This ranged from £7.85 (England and Wales) to £9.16 (Northern Ireland) per patient visit ($10.20 to $11.90, respectively) meaning the incremental cost for six month in a cavity‐free state ranged from £261.67 ($339.93) in England and Wales to £305.33 ($369.68) in Northern Ireland. Further, changes in baseline assumptions and parameter values did not change mid‐level providers being the dominant service intervention. Conclusion: In a time of limited funds for dental services, these results suggest that resources in public funded systems could be saved using mid‐level providers in dental practices, without any health risk to patients or capital investment.